The Influence of Oil Prices, Gold Prices, and Inflation on the Indonesian Sharia Stock Index 2021-2025 - Sri Nawatmi Nawatmi; Agung Nusantara; Ali Maskur; Mulyo Budi Setiawan (International Journal of Multidisciplinary Sciences and Arts, 2025)
As is known, the stock price index always fluctuates. Fluctuations are sometimes high, sometimes low, and sometimes it is difficult to predict the rise and fall of the stock index. Therefore, the purpose of this study is to determine how the variables of world oil prices, world gold prices and inflation affect the Indonesian sharia stock index (ISSI). The type of data is secondary data. The data taken is time-series data, the time period January 2021 - February 2025. The dependent variable is ISSI, while the independent variables are world oil prices, world gold prices and inflation. Data sources come from BPS (Central Statistics Agency), BI (Bank Indonesia) and investing.com. The analysis method used is the OLS (Ordinary Least Square) method with multiple linear regression techniques. Before analyzing, classical assumption detection was carried out starting from the detection of normality, multicollinearity, heteroscedasticity and autocorrelation. The estimation results show that the world oil price variable does not affect the movement of the ISSI, while the world gold price and inflation have a positive effect on the Indonesian sharia stock index.